Antegrade Hepatic Artery and Portal Vein Perfusion Versus Portal Vein Perfusion Alone in Living Donor Liver Transplantation: A Randomized Trial. Issue 9 (18th July 2019) - Shaji Mathew, Johns; Kumar, K.Y. Santosh; Nair, Krishnanunni; Thankamony Amma, Binoj Sivasankara Pillai; Krishnakumar, Lakshmi; Balakrishnan, Dinesh; Gopalakrishnan, Unnikrishnan; Menon, Ramachandran Narayana; Sunny, Aleena; Dhar, Puneet; Othiyil Vayoth, Sudheer; Surendran, Sudhindran
Abstract : Traditionally, deceased donor liver grafts receive dual perfusion (DP) through the portal vein and the hepatic artery (HA) either in situ or on the back table. HA perfusion is avoided in living donor liver grafts for fear of damage to the intima and consequent risk of hepatic artery thrombosis (HAT). However, biliary vasculature is predominantly derived from the HA. We hypothesized that antegrade perfusion of the HA in addition to the portal vein on the back table could reduce the incidence of postoperative biliary complications. Consecutive adult patients undergoing living donor liver transplantations were randomized after donor hepatectomy to receive graft perfusion of histidine‐tryptophan‐ketoglutarate solution either via both the HA and portal vein (DP group, n = 62) or only through the portal vein (standard perfusion [SP] group, n = 62). The primary endpoint was the occurrence of biliary complications (biliary leak/stricture). Secondary endpoints included HAT and patient survival. The incidence of biliary stricture was significantly lower in the DP group (6.5% versus 19.4%; odds ratio, 0.29; 95% confidence interval, 0.09‐0.95; P  = 0.04). There was no significant reduction in the incidence of HAT, bile leak, or hospital stay between the 2 groups. The 3‐year mortality and graft survival rates were significantly higher among patients who received DP compared with SP ( P  = 0.004 and P  = 0.003, respectively). On multivariate analysis, nonperfusion of the HA and preceding bile leak were found to be risk factors for the development of biliary stricture ( P  = 0.04 and P  < 0.001, respectively). In conclusion, DP of living donor liver grafts through both the HA and portal vein on the back table may protect against the development of biliary stricture. This could translate to improved patient survival in the short term.